46.0k views
2 votes
What is the solution for 11 = y-6

2 Answers

11 votes

Hello.

Let's solve this equation for y.

First, subtract 11 from both sides:


\mathrm{11-11=y-6-11}


\mathrm{0=y-6-11}


\mathrm{0=y-17}

Subtract y from both sides:


\mathrm{-y=-17}


\Large\boxed{\sf{y=17}}

I hope it helps.

Have a nice day.


\boxed{imperturbability}

User Ogbofjnr
by
4.8k points
12 votes

Answer:

y = 17

Explanation:

11 = y - 6

  • 11 + 6 = y
  • 17 = y

prove that the value of y is 17

11 = y - 6

  • 11 = 17 - 6
  • 11 = 11

proven

User Trevor Powell
by
5.6k points